The Effect of Performance Anticipation on Students’ Recognition in Online Learning - Katherine Ronauly Maharani Silaban; Wilis Srisayekti; Windy Nathasya Saputra; Gabriella Samantha Carmella; Alifatunnisa Hafidza; Rausyan Fikri Muhammad Ilham; Fanny Rizkiyani; Nurul Izzah Binti Shari (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2024)
This experimental research investigated the effect of performance anticipation on students recognition in the context of online learning. Data were collected through online presentation via Zoom and analyzed with between-participants posttest-only control group design. The data collected comprised 69 students aged 17 to 20 years with mean and SD of 18.09 years and 0.59, respectively. The confederate, experimental, and control groups conducted the presentation in the first, second, and zero order. The results showed a significant difference between the control and experimental groups in recognition scores (p = .011), which decreased performance anticipation of student’s recognition ability in online learning contexts. The findings can be utilized by educators to design learning scenarios needed to optimize students understanding of presentation materials and lectures. Furthermore, presentations should be scheduled at the beginning of the class and limited to one per session.